All Together Now: Impact of a Regionalization and Bedside Rounding Initiative on the Efficiency and Inclusiveness of Clinical Rounds. Issue 3 (1st March 2017) - Huang, Kristin T. L.; Minahan, Jacquelyn; Brita‐Rossi, Patricia; Aylward, Patricia; Katz, Joel T.; Roy, Christopher; Schnipper, Jeffrey L.; Boxer, Robert
Abstract : BACKGROUND: Attending rounds at academic medical centers are often disconnected from patients and team members who are not physicians. Regionalization of care teams may facilitate bedside rounding and more frequent interactions among doctors, nurses, and patients. OBJECTIVE: We used time–motion analysis to investigate how regionalization of medical teams and encouragement of bedside rounds affect participants on rounds and rounding time. DESIGN AND SETTING: We used pre–post analysis to study the effects of care redesign on teams' daily rounds on a general medicine service at an academic medical center. PARTICIPANTS: Four general medical teams were evaluated before the intervention and 5 teams afterward. INTERVENTIONS: General medical teams were regionalized to specific units, the admitting structure was changed to facilitate regionalization, and teams were encouraged to round bedside. MEASUREMENTS: Primary outcomes included proportion of time each team member was present on rounds and proportion of bedside rounding time. Secondary outcomes included round duration and non‐patient time during rounds. RESULTS: Proportion of time the nurse was present on rounds increased from 24.1% to 67.8% ( P < 0.001), and proportion of total bedside rounding time increased from 39.9% to 55.8% ( P < 0.001). Mean total rounding time decreased from 3.0 hours to 2.4 hours ( P = 0.01), despite a higher patient census. CONCLUSIONS: Creating regionalized care teams and encouraging interdisciplinary bedside rounds increased the proportion of bedside rounding time and the presence of nurses on rounds while decreasing total rounding time.